Analisis Strategi Peningkatan Pelayanan Air Bersih Pdam Tirta Dharma Kecamatan Tanjung Kabupaten Tabalong - Nurhalisah Nurhalisah; Emmy Lilimantik; Rukmini Rukmini; Leila Ariyani Sofia (Universitas Lambung Mangkurat, 2021)
The management of clean water by PDAM is almost spread throughout Indonesia, but its distribution has not yet reached all regions. PDAM Tirta Dharma is a business entity owned by the Tabalong Regency Government which is responsible for providing services and smooth distribution of clean water to the community in Tanjung District. The research objective was to analyze the strategy for improving PDAM clean water services with the object of research being in Tanjung District. The sampling method used in this research is the Stratified Random Sampling technique, and the data collection uses a questionnaire method and the measurement method uses a Likert Scale / Ratting Scale (multilevel scale) filled with respondents who are PDAM Tirta Dharma customers, household customers class A1, A2 and A3. The strategy for improving PDAM clean water services with a SWOT analysis, namely: the latest technology updates to support maintenance and repair of PDAM utilities, additional backup power itself according to the PDAM's IPA capacity, expansion of the PDAM water pipe network, regular checks on the quality of raw water from Tabalong river and clean water processed by PDAM, as well as the addition of field technicians in the division of certain areas.